Efeitos renais de complexos de rutênio e sua ação na proteção da lesão aguda induzida por isquemia e reperfusão - Alves, Natacha Teresa Queiroz (2018)
In endothelial cells, the nitric oxide (NO) is the main responsible for the maintenance of vascular homeostasis. Ischemia/reperfusion injury (I/R) is a common cause of acute renal injury in clinical settings. Studies with nitrosyl ruthenium complexes have shown protection in the cerebral ischemia/reperfusion model, as well as anti-inflammatory and antioxidant properties in a gastric lesion model. The aim of this study was to investigate the renal effects of ruthenium complexes (FOR 811A and FOR 011 A) and its possible nephroprotective effects in the treatment of renal pathologies involving the NO/GCs/cGMP pathway. In order to evaluate the renal hemodynamic effects of ruthenium complexes, isolated kidney perfusion experiments were performed and biochemical parameters were analyzed for the samples collectedand quantification of cGMP by ELISA. I/R model in vitro were performedin LLC-MK2 renal tubule cells line and cell respiration assay by flow cytometry.In vivo I/R model with right nephrectomy and renal artery clamping was performed, besides biochemical analyses,oxidative stressand immunohistochemistry for iNOS and TNF-α.The project was approved by the EthicsCommittee on Use of Animals (CEUA)/UFC under protocol number 83/2017.In isolated kidney perfusion, the compounds FOR 811 A (1,0 μmol/L) and FOR 011 A (1,0 μmol/L) promoted increase perfusion pressure, renal vascular resistance and urinary flow. The FOR 811 A (0,3 μmol/L,1,0 μmol/L) decreased the total and proximal transports of sodium, potassium and chloride.The SNP and FOR 811 A groups (both concentrations) increased cGMP levels in the perfused kidneys.Thefore, the FOR 011 decreased in total and proximal transport of sodium and chloride. In LLC-MK2 cells line, only FOR 811 A demonstrated potential protective effect of respiratory dysfunction caused by I/R injury. In I/R model in vivo, the treatment with FOR 811 A decreased serum creatinine levels, urea and fraction of excretion of sodium and potassium. In comparison to group I/R, the I/R 811 A did not alter the nitrite/nitrate levels, increased GSH levels, decreased marking iNOS and TNF-α by immunohistochemistry. Therefore, the 811 A showed changes in renal hemodynamics that appear to be mediated by the activation of GCs, antioxidant properties and protective effect against nephrotoxicity parameters.